The technical and tactic analysis of Zhang Jike's performance in Paris World Table Tennis Championships - Zhang Jike vs Baum Patrick - Huang, W.; Li, T.; Chen, L. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
1. Purpose: Zhang Jike, the famous Chinese table tennis player, won the grand slam, when he has got the champions in 2011 World Championships, 2011 World Cup and 2012 London Olympics. Zhang performed extraordinary well in 2013 Paris World Championships and won the champion for men single. The study analysed Zhang`s performance, trying to provide some scientific basis for his future technical and tactic training. 2. Methods: The study selected Zhang`s 1 important matches in the championships in Paris - the quarter finals Zhang Jike vs Baum with a 4-1 score. By calculating the scoring rate and the utility rate of Zhang`s first/third strike and second/fourth strike, as well as the rate trend, the study tried to analyse his technical and tactic practice. 3. Results and Discussion (1) Zhang owned a strong spirit of winning in the matches, combined with a long duration of excitement point and comprehensive strength. During the process, he played the style of violent attack as well as the reason and patience. All of them contributed to his success. (2) Zhang adopted inside out service to fit the back-top spin, which created opportunities for the attack after service in the third strike. He received with backhand twist pulling the ball to the opponent`s side, which easily won the advantage and score accordingly. During the topspin confrontation, he changed the playing by adjusting the forehand and pressing backhand, in addition to the changes of spin and rhythm, thus he produced great pressure on the opponent. (3) When meeting with strong resistance, Zhang tended to responded slowly, this could create difficulty for himself. Key words: table tennis, Zhang Jike, World Table Tennis Championships, technical and tactic analysis